Code Status Reconciliation to Improve Identification and Documentation of Code Status in Electronic Health Records - Jain, Viral G; Greco, Peter J; Kaelber, David C (Applied Clinical Informatics, 2017)
Background: Code status (CS) of a patient (part of their end-of-life wishes) can be critical information in healthcare delivery, which can change over time, especially at transitions of care. Although electronic health record (EHR) tools exist for medication reconciliation across transitions of care, much less attention is given to CS, and standard EHR tools have not been implemented for CS reconciliation (CSR). Lack of CSR creates significant potential patient safety and quality of life issues. Objective: To study the tools, workflow, and impact of clinical decision support (CDS) for CSR. Methods: We established rules for CS implementation in our EHR. At admission, a CS is required as part of a patient’s admission order set. Using standard CDS tools in our EHR, we built an interruptive alert for CSR at discharge if a patient did not have the same inpatient (current) CS at discharge as that prior to admission CS.Results: Of 80,587 admissions over a four year period (2 years prior to and post CSR implementation), CS discordance was seen in 3.5% of encounters which had full code status prior to admission, but Do Not Resuscitate (DNR) CS at discharge. In addition, 1.4% of the encounters had a different variant of the DNR CS at discharge when compared with CS prior to admission. On pre-post CSR implementation analysis, DNR CS per 1000 admissions per month increased significantly among patients discharged and in patients being admitted (mean ± SD: 85.36 ± 13.69 to 399.85 ± 182.86, p<0.001; and 1.99 ± 1.37 vs 16.70 ± 4.51, p<0.001, respectively).Conclusion: EHR enabled CSR is effective and represents a significant informatics opportunity to help honor patients’ end-of-life wishes. CSR represents one example of non-medication reconciliation at transitions of care that should be considered in all EHRs to improve care quality and patient safety.
Keywords: Code status; advance directive; meaningful use; reconciliation; medication; DNR